Maternal knowledge, perception, and attitude regarding the management of childhood febrile illness - Nazme , Nure Ishrat; Islam, Md Khademul (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background:Maternal knowledge, perception, and attitude play a crucial role in the effective management of childhood febrile illnesses, as mothers are often the primary caregivers. Understanding how mothers recognize, interpret, and respond to fever can influence the timely administration of appropriate care. This highlights the importance of educating mothers on fever management practices to improve health outcomes for children. Objective:The aim is to assess maternal perceptions on the home management of childhood fever, focusing on their understanding and practices in addressing febrile illness in children. This insight can guide strategies to improve care and health outcomes. Materials and Methods: This cross-sectional study was conducted at the Pediatric Outpatient Department (OPD) of CMH Ramu, Ramu Cantonment, from April 2024 to July 2024 on 350 mothers attending with a feverish child under twelve years. Results:In our study, 60% of mothers used their hands to measure their child's body temperature, with the armpit being the preferred site. The definition of fever varied among mothers, ranging from ≥98°F to 102°F. A large proportion, 86%, were unaware of the proper dosing and frequency of Paracetamol, while 90% consulted a doctor before administering any antipyretic. The oral route was favored by 89% of mothers for antipyretic administration, and 14% relied on traditional methods. Paracetamol was the most commonly used antipyretic in 91% of cases, while 51% of mothers preferred antibiotics at the onset of fever to prevent its progression. Cefixime was the most frequently selected antibiotic (44.4%), followed by Azithromycin (30.6%) and other options. Conclusions: Misconceptions about the management of febrile children are widespread among mothers in Bangladesh, leading to unnecessary concern and an increased burden on healthcare facilities. There is a pressing need to enhance their knowledge and perception to improve care and reduce this strain. J Bangladesh Coll Phys Surg 2025; 43: 39-45